Українська соціал-демократія в суспільно-політичному житті ЗУНР (листопад 1918 р. – липень 1919 р.) - Райківський, І. (Україна: культурна спадщина, національна свідомість, державність, 2009)
Досліджено діяльність української соціал-демократичної партії в суспільно- політичному житті ЗУНР, виділено опозиційне ставлення УСРП до УНРади і уряду ЗОУНР після підписання Акту злуки 22 січня 1919 р., ініціювання створення Селянсько-робітничого союзу. The article investigates the role of the Ukrainian Social-Democratic party in the socio-political life of the West Ukrainian People’s Republic. The author emphasizes the oppositional attitude of the Ukrainian Socialist Radical Party towards the Ukrainian National Council and the Government of the Western Provinces of Ukrainian People’s Republic after the Act Zluky was signed on the 22nd of January 1919. The article also focuses on the instigation of the establishment of the Peasant-Worker’s Union.